Smoking Prevalence among Teenagers with Asthma in Lattakia Schools - ديب غزل; الحكيم أمل; حشمة علا (Latakia University Journal -Medical Sciences Series, 2020)
Asthma is a widespread and chronic disease that affects adolescence and lifestyle effectiveness other than the enormous economic cost of treating cases and their complications in the short and long term.